1997
DOI: 10.1152/ajpcell.1997.273.6.c1963
|View full text |Cite
|
Sign up to set email alerts
|

Functional ATP receptors in rat anterior pituitary cells

Abstract: The effects of ATP and other nucleotides on the cytosolic Ca2+ concentration ([Ca2+]i) of single immunocytochemically typed anterior pituitary (AP) cells have been studied. ATP increased [Ca2+]iin a large percentage (60–88%) of all five AP cell types: lactotropes, somatotropes, corticotropes, gonadotropes, and thyrotropes. Additivity experiments suggest the presence of at least two different receptors, one accepting both ATP and UTP (U receptor), producing Ca2+ release from the intracellular stores, and the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…This is consistent with the notion that binding of growth hormone-releasing hormone to its receptor activates not only the stimulatory subunit a of the G-protein (Ga-S, cAMP-dependent pathways) but also Ga-I, Gb, and Gg, leading to release of intracellular free Ca 2C , which then further triggers secretion of GH (44,45). Moreover, ATP, which is co-released with pituitary hormones, induces an increase in free Ca 2C in pituitary cells (46). These data strongly suggest that dysregulation of the calcium signaling might be an important co-signal in somatotrophs and potentially involved in pituitary tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the notion that binding of growth hormone-releasing hormone to its receptor activates not only the stimulatory subunit a of the G-protein (Ga-S, cAMP-dependent pathways) but also Ga-I, Gb, and Gg, leading to release of intracellular free Ca 2C , which then further triggers secretion of GH (44,45). Moreover, ATP, which is co-released with pituitary hormones, induces an increase in free Ca 2C in pituitary cells (46). These data strongly suggest that dysregulation of the calcium signaling might be an important co-signal in somatotrophs and potentially involved in pituitary tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Using the technique of single-cell calcium measurement, the initial characterization of purinoceptors in anterior pituitary cells were identified [2][3][4][5][6]. These experiments revealed that functional P2X receptors are operative in all secretory cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular cloning and functional characterization of rat P2YRs in the pituitary revealed the expression of P2Y 2 R with the pharmacological profile resembling the one observed in sheep pituitary cells (15). More recent studies have also suggested the presence of P2XRs in normal and immortalized pituitary cells (4,16,17). Initially, the mRNA messages for P2X 2a R and its spliced form, P2X 2b R, were identified in pituitary cells (18 -20).…”
mentioning
confidence: 96%